Nationalist historiography and revisionism in Peru in the mid-20th century: Pablo Macera and his representation of the precursors of independence - Loayza Pérez, Alex (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This article presents an overview of Latin American and Peruvian historiography of the Enlightenment in the 1950s. It is argued that in Peru there was a traditional vision of the Enlightenment that connected it directly with the independence process by locating in it the development of a national consciousness in the Creole elite. This perspective was articulated with the official discourse that attributed a heroic character to them: the Peruvian Creoles were the «precursors» of Peruvian independence. In his high school thesis, Pablo Macera criticized this nationalist discourse by showing that the heroic representation of the Creole «precursors» hid the fact that they were economically, socially, and politically conservative, not revolutionary. Macera, in contrast to the precursors, identified other minor actors who would be more «revolutionary» in their ideas and political proposals. Likewise, this thesis presents an early questioning of the traditional history of ideas current in Latin America by basing itself on the sociology of knowledge that allows it to pay attention to the social and discursive context of the thought and action of the Lima Creoles of the 18th century. Based on these approaches, it is argued that Macera's work can be located within a revisionist historiographical discourse.